The role of Th-17 cells and IL-17 in the metastatic spread of breast cancer: As a means of prognosis and therapeutic target - Shibabaw, Tewodros; Teferi, Banchamlak; Ayelign, Birhanu (Frontiers in Immunology, 2023)
Metastatic breast cancer is one of the most common and well-known causes of death for women worldwide. The inflammatory tumor cell and other cancer hallmarks dictate the metastatic form and dissemination of breast cancer. Taking these into account, from various components of the tumor microenvironment, a pro-inflammatory infiltrative cell known as Th-17 plays an immense role in breast cancer proliferation, invasiveness, and metastasis. It has been demonstrated that IL-17, a pleiotropic pro-inflammatory cytokine generated by Th-17, is upregulated in a metastatic form of breast cancer. Recent research updates stated that chronic inflammation and mediators like cytokines and chemokines are causative hallmarks in many human cancers, including breast cancer. Therefore, IL-17 and its multiple downward signaling molecules are the centers of research attention to develop potent treatment options for cancer. They provide information on the role of IL-17-activated MAPK, which results in tumor cell proliferation and metastasis via NF-kB-mediated expression of MMP signaling. Overall, this review article emphasizes IL-17A and its intermediate signaling molecules, such as ERK1/2, NF-kB, MMPs, and VEGF, as potential molecular targets for the prevention and treatment of breast cancer.